Pengaruh Literasi Keuangan, Akses Paylatter Dan Keinginan Terhadap Perilaku Implusif Buying Dengan Gaya Hidup Sebagai Variabel Moderasi (Studi Pada Muhammadiyah Bisnis Center (MBC) Kota Metro) - Ardiyanti, Novita; Nasikah, Durotun (Universitas Muhammadiyah Metro, 2022)
ABSTRACT Student lifestyles have changed where this change is not caused by changing needs but is more influenced by the development of the consumptive world of social media. This study aims to determine the effect of financial literacy, ease of paylater access, wants and needs on consumptive behavior with lifestyle as a mediating variable. Research design is quantitative research or verification research. The method used in this research is financial literacy, easy access to paylater, wants and needs, consumptive behavior and lifestyle. The population and research sample were students of the Management Study Program 2018 with a total sample of 68 students. Data collection techniques using questionnaires. The analytical tools used are data quality analysis and Moderated Regression Analysis (MRA) with the SPSS program.The results showed that financial literacy had no effect on consumptive behavior. Ease of access to paylater, and partial desire have a positive and significant effect on consumptive behavior. improve student consumptive behavior. Financial literacy, easy access to paylater, and desire simultaneously have a positive and significant influence on consumptive behavior. Lifestyle moderates or increases the influence of financial literacy, ease of paylater access, and the desire for consumptive behavior. Keywords: Financial Literacy, Ease of Paylater Access, Desire, Consumptive Behavior, Lifestyle